Persepsi dan Hambatan Siswa terhadap Pelaksanaan Senam Aerobik dalam Pembelajaran PJOK di Sekolah Banda Aceh - Fajri, Mahlil; Rozalini, Novia; Fadly, Hendry; Imam Bahesty, Dicky (Jurnal Muara Olahraga, 2025)
Aerobic gymnastics in Physical Education, Sports, and Health (PJOK) has the potential to improve physical fitness, enthusiasm for learning, and student participation. These obstacles include limited time during PJOK hours, inadequate facilities and space, students' lack of self-confidence, lack of motivation, and teachers' limited ability to provide interesting learning variations. This study aims to determine students' perceptions and identify obstacles regarding the implementation of aerobic gymnastics as part of PJOK learning in Banda Aceh schools. This type of research uses a survey method with a questionnaire instrument, the number of respondents is 100 students from several schools in Banda Aceh using the Stratified Random Sampling technique. Descriptive statistical analysis to describe students' perceptions and obstacles towards the implementation of aerobic gymnastics in PJOK learning. The results of the study students have a positive view of the benefits of aerobic gymnastics, especially in the aspects of health and fitness, increased concentration, and a pleasant learning environment. However, the most frequently experienced challenges are limited time for PJOK lessons, inadequate facilities and space, and students' shyness or low motivation, especially when having to perform movements with complicated choreography or when performing in front of friends. that positive views are significantly related to motivation and frequency of participation in aerobic gymnastics